UPAYA PEMERINTAH KAMBOJA DALAM MENANGANI KASUS PERDAGANGAN MANUSIA DI KAMBOJA TAHUN 2022-2023 - Siagian, Rizky Meliana; Pakpahan, Saiman (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
Human trafficking is a complex issue that requires a strategic government response. This phenomenon is even more crucial in Cambodia, which acts as a country of origin, transit and destination. This study analyzes the Cambodian government's concrete steps at the national, bilateral, regional and multilateral scales. The research method is a descriptive qualitative approach based on document analysis. This research uses K.J Holsti's theory of international cooperation. The results of this study show Cambodia's commitment through strengthening the legal framework and ratification of international instruments (UNTOC, ILO, ACTIP) as well as the implications of the TSE Law in the national legal framework. Cambodia makes various domestic and international efforts through bilateral, regional and multilateral cooperation. However, implementation is constrained by capacity gaps, inter-agency coordination and systematic corruption, requiring an integrated and sustainable approach to address the structural problems of combating human trafficking in Cambodia. Keywords: Human Trafficking, Transnational Crime, International Cooperation, National Interest.